O-6 Delivering integrated hospice based care in motor neurone disease. Issue Volume 6: Issue (2016)Supplement 1 (1st November 2016) - Ferguson, Claire; McArthur, Suzanne; Reed, Nikki
Abstract : Background: 2016 NICE guidelines on assessment and management of Motor Neurone Disease (MND) recommend that patients should have access to multidisciplinary, integrated care with access to local services and support groups. Feedback from patients and carers at our hospice-based MND support group highlighted that although the tertiary hospital clinic was important to them, it lacked access to local support, and pre-bereavement care. Often crises and issues arise in between hospital appointments; therefore local services are important in hospital admission avoidance where possible. Aim: To develop a satellite MND MDT clinic at our hospice incorporating the regional and local MND expertise. Method: The novel hospice-based clinic includes the hospital MND specialist nurse, an MND Association representative, and the hospice therapy team. New referrals are seen in the next monthly clinic. The pilot will run for 12 months and be reviewed at six and 12 months. During the year, clinic activity data, patient and carer feedback and a patient reported outcome scale (IPOS) will be collected as part of the service evaluation. This service is being set up within existing hospice budgets. Results: Preliminary analysis of IPOS and qualitative feedback data indicates that patients and carers prefer not having the burden of travelling to the tertiary hospital and value the opportunity to have more time to discuss their care and access the local services available to them. Frequent reviews and expedited access to hospice services has allowed more timely management of arising issues, preventing interval hospital admissions. Conclusions: By implementing the 2016 NICE Guidelines in MND care through our novel hospice-based clinic, we have a new service which rates very highly in satisfaction with patients and carers. It is also preventing crises in MND care falling upon tertiary centres by diversion to palliative care within local services.